Anemia of chronic diseases: the important aspects of pathogenesis and treatment - O. A. Rukavitsyn (Онкогематология)
The review contains data about new important aspects of pathogenesis, and treatment of anemia of chronic diseases. The treatment of patients with anemia of chronic diseases by erythropoiesis-stimulating agents and iron is analyzed.